The Influence Of Digital Marketing And E-Learning Platform Quality On Subscription Interest In My Skill Platform: Pengaruh Digital Marketing dan Kualitas Platform E-Learning Terhadap Minat Berlangganan Pada Platform My Skill - Rahma, Fanny Aulia; Athar, Handry Sudiartha (Jurnal Pijar, 2025)
This study aims to examine the influence of digital marketing and e-learning platform quality on users subscription interest in My Skill platform. The research employs a quantitative approach with a survey method, involving 100 respondents selected through purposive sampling. Primary data were collected using closed-ended questionnaires with a Likert scale and analyzed using multiple linear regression techniques to assess the relationships between variables. The results indicate that digital marketing and e-learning platform quality significantly and positively influence users' subscription interest in My Skill platform. Digital marketing and e-learning platform quality contribute 77.9% to subscription interest. The findings suggest that implementing effective digital marketing strategies and improving e-learning platform quality that meets users' expectations and needs can enhance users' subscription interest.